2012
DOI: 10.2217/pme.12.3
|View full text |Cite
|
Sign up to set email alerts
|

Ascertainment and Critical Assessment of the Views of the General Public and Healthcare Professionals on Nutrigenomics in Greece

Abstract: Executive Summary There is an urgent need to critically assess the nutrigenomics field, particularly since the general public is often misinformed about the potential benefits of correlating an individual's genomic genetic profile with their nutritional status. In this article, we attempt to shed light on the views and perceptions of healthcare professionals and the general public in relation to nutrigenomics, to investigate how a healthcare professional might include genetic testing in routine health examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 24 publications
4
21
0
3
Order By: Relevance
“…Some preferred personalised nutrition to be delivered as part of existing health services, while others favoured the anonymity and convenience afforded by commercial offerings (Berezowska et al, 2014;Fallaize et al, 2015;Stewart-Knox et al, 2014;. This finding was novel given that previous studies have unanimously implied that the public would prefer services to be delivered through existing health provision (Pavlidis et al, 2012;Su and Lu, 2012;Wendel et al, 2013). The Food4me survey confirmed that a large proportion of Europeans preferred health service provision, but also identified a second potential market comprised of those who preferred the anonymity and degree of control that D-T-C personalised nutrition would afford (Food4me White Paper, 2015).…”
Section: Trust In Potential Providers Of Personalised Nutritionmentioning
confidence: 94%
“…Some preferred personalised nutrition to be delivered as part of existing health services, while others favoured the anonymity and convenience afforded by commercial offerings (Berezowska et al, 2014;Fallaize et al, 2015;Stewart-Knox et al, 2014;. This finding was novel given that previous studies have unanimously implied that the public would prefer services to be delivered through existing health provision (Pavlidis et al, 2012;Su and Lu, 2012;Wendel et al, 2013). The Food4me survey confirmed that a large proportion of Europeans preferred health service provision, but also identified a second potential market comprised of those who preferred the anonymity and degree of control that D-T-C personalised nutrition would afford (Food4me White Paper, 2015).…”
Section: Trust In Potential Providers Of Personalised Nutritionmentioning
confidence: 94%
“…Finally, the lack of regulation shows that there are no specific recommendations and guidelines till now in order to apply these tests in everyday life. It seems also that health professionals, but also in some cases the general public, are not totally ready for the use of these tests or they cannot fully understand or interpret them (Pavlidis et al, 2012). The need for an enhanced education/training on this field as well as data interpretation became evident in our previous study on nutrigenomics perceptions and views in Greece (Pavlidis et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…It seems also that health professionals, but also in some cases the general public, are not totally ready for the use of these tests or they cannot fully understand or interpret them (Pavlidis et al, 2012). The need for an enhanced education/training on this field as well as data interpretation became evident in our previous study on nutrigenomics perceptions and views in Greece (Pavlidis et al, 2012). On the other hand, extra care should be given when these tests are prescribed, as their use is not yet well defined by law and by the scientific community through clinical research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations